Cell cycle in development - Kubiak, Jacek Z.; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book focuses on the intersection between cell cycle regulation and embryo development. Specific modifications of the canonical cell cycle occur throughout the whole period of development and are adapted to fulfil functions coded by the developmental program. Deciphering these adaptations is essential to comprehending how living organisms develop. The aim of this book is to review the best-known modifications and adaptations of the cell cycle during development. The first chapters cover the general problems of how the cell cycle evolves, while consecutive chapters guide readers through the plethora of such phenomena. The book closes with a description of specific changes in the cell cycle of neurons in the senescent human brain. Taken together, the chapters present a panorama of species - from worms to humans - and of developmental stages - from unfertilized oocyte to aged adult.
Experimental systems to explore life origin: perspectives for understanding primitive mechanisms of cell division. Evolution of bet-hedging mechanisms in cell cycle and embryo development stimulated by weak linkage of stochastic processes. Mechanics of cell shape regulation during the cell cycle. The spindle assembly checkpoint: clock or domino? Cell-size-dependent control of organelle sizes during development. The first cell cycle of the C. elegans embryo. Spatial and temporal control of an asymmetric cell division. EGG Molecules Couple the Oocyte-to-Embryo Transition with Cell Cycle Progression. Cell cycle in ascidian eggs and embryos. Regulatory Pathways Coordinating Cell Cycle Progression in Early Xenopus Development. Control of DNA replication by Cyclin-Dependent Kinases in development. Greatwall kinase, ARPP-19 and protein phosphatase 2A: shifting the mitosis paradigm. The Role of RanGTP Gradient in Vertebrate Oocyte Maturation. Cell Cycle Control of Germ Cell Differentiation. Protein kinases and protein phosphatases that regulate meiotic maturation in mouse oocytes. Anaphase-Promoting Complex control in female mouse meiosis. Established and novel Cdk/cyclin complexes regulating the cell cycle and development. Function of the A-type Cyclins during Gametogenesis and Early Embryogenesis. Cell cycle adaptations and maintenance of genomic integrity in embryonic stem cells and induced pluripotent stem cells. Cell cycle regulation by microRNAs in stem cells. Cell cycle regulation during proliferation and differentiation of mammalian muscle precursor cells. Drosophila neural stem cells: cell cycle control of self-renewal, differentiation and termination in brain development. Control of neuronal ploidy during vertebrate development. Cell Cycle Deregulation in the Neurons of Alzheimer?s Disease.
Electronic reproduction.
Keywords: Cell cycle -- Physiology; Embryology -- Physiology; Neurons -- Physiology; Cell cycle -- Physiology; Embryonic development -- Physiology; Neurons -- Physiology; Electronic books